If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2Y = 150 Reorder the terms: -2Y + 3x = 150 Solving -2Y + 3x = 150 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-3x' to each side of the equation. -2Y + 3x + -3x = 150 + -3x Combine like terms: 3x + -3x = 0 -2Y + 0 = 150 + -3x -2Y = 150 + -3x Divide each side by '-2'. Y = -75 + 1.5x Simplifying Y = -75 + 1.5x
| 2.9x=27.55 | | 4.8x=40.8 | | 24x^3+36x^2= | | 3X=2Y+150 | | 2x+12=12-10x | | x(-15x-64)-33=0 | | -9-6x=5x+14 | | (x+3/3)-(x-1/2)=4 | | 5y^2-4y-30=0 | | y^2-x^2-12y-8x-16=0 | | 16(x+1)-2(3-x)=-3(x+6) | | x+3+3(x+2)=9-2x | | 10x+4(-3x+1)-1=2x-(4x+1) | | 5+6(x+3)=4(x-1)+7 | | 4,6+z=5,6-3z | | 0,2x+2,5=1,5x-10,5 | | -y+2=-2y+0,5 | | 1,5p-2,3=-2,3+4p | | x^2dy-y^2dx=0 | | 9p+79= | | 2x-4=9x-28 | | 8x^2+x+63=0 | | -16t^2+144t-s=0 | | (x+1)/(x-4)=1 | | (x+1)/(x-4)-1=0 | | 100x-x^3=0 | | (x+4)(2x+2)(3x-3)=0 | | 7w^2+4w-16=0 | | 2x^2+9+5=0 | | Y=8x^2+22x-6 | | 6.75=2.75x+.10 | | 6x^2+11x+6=0 |